Enhancing the Daftardar Jafari Method for Solving the Bagley–Torvik Equation through Numerical Approaches - Saje, A. A; Kwami, A. M; Madaki, A. G; O, Okai J.; Waziri, I. M.; Hafsat, Yakubu (Darul Yasin Al Sys, 2025)
A robust algorithm is introduced in the development of the Enhanced Daftardar Jafari Method (DJM) to effectively address both linear and nonlinear Bagley–Torvik equations (BTE) and other fractional order differential equations. The method's efficacy is demonstrated through numerical examples, showcasing its ability to solve these equations without resorting to linearization or small perturbations. The results affirm the method's strength, accuracy, and simplicity in comparison to alternative approaches.